(untitled) (Journal of Enam Medical College, 2019)
Intestinal tuberculosis (TB) most commonly affects ileo-caecal region. Isolated gastric and duodenal involvement without pulmonary infection is rare. The presentation of these patients varies. Patients may present with haematemesis, non-healing chronic ulcer, mimicking malignancy, gastric perforation and gastric outlet obstruction. High degree of suspicion is needed for early diagnosis of gastro-duodenal TB. A young female patient who was being treated as a case of nonhealing chronic ulcer was referred for treatment. Histopathological examination of endoscopic biopsy specimen of the patient showed presence of granulomas composed of epitheloid cells and Langhan’s giant cells with caseation with no evidence of tuberculosis at pulmonary or other body sites. After anti-tubercular chemotherapy there was resolution of symptoms and healing of ulcers. This case of isolated gastro-duodenal TB is reported for its rarity. J Enam Med Col 2019; 9(3): 189-192